Ответ:
Г (2;10)
Пошаговое объяснение:
Условие перпендикулярности 2-х прямых у=а₁х+b₁ у=а₂х+b₂
а₁*а₂=-1
прямая у=-х/8+1/4 a1=-1/8
для касательной определим производную
у'=6x-4 y = f(x₀) + f’(x₀)*(x - x₀).
y = f(x₀) + f’(x₀)*(x - x₀).
y =f’(x₀)*x+f(x₀)-f’(x₀)*x₀
У второй прямой а₂=f’(x₀)=6x₀-4
(6x₀-4)*(-1/8)=-1
6x₀-4=8
x₀=(8+4)/6=2
f(x₀)=f(2)=3*4-4*2+6=10
(2;10)
1) 16:4*7=28(м)
2) 12:3*4=16(т)
3) 4:2*3=6(ч)
2х^2+20+50=2(х^2+10х+25)=2(х+5)^2
с^8-81=(с^4-9)(с^4+9)=(с^2-3)(с^2+3)(с^4+9)
4х^2+4х-у^2+1=(2х+1)^2-у^2=(2х+1-у)(2х+1+у)